Penguatan Literasi Parenting melalui Edukasi Neurosains dalam Pengasuhan Islami pada Anggota Pimpinan Cabang Nasyiatul Aisyiyah Doro - Gigih Setianto; Aisyah Dzil Kamalah; Risdiani Risdiani (Universitas Negeri Gorontalo, 2026)
Early childhood parenting is critical for supporting brain development and shaping children's cognitive, socio-emotional, and character development. However, many parents still rely on personal experience rather than scientific knowledge of brain development, indicating the need to strengthen parenting literacy through a neuroscience-based approach integrated with Islamic values. This community service program aimed to improve the parenting literacy of members of the Doro Branch of Nasyiatul Aisyiyah (PCNA Doro). Twenty-one active members, consisting of mothers and prospective mothers, participated in a participatory educational program involving interactive lectures, group discussions, case studies, reflective learning, and the distribution of a Brain-Based Islamic Parenting leaflet. Program effectiveness was evaluated using a one-group pretest-posttest design and analyzed through descriptive statistics and a paired-samples t-test. The mean knowledge score increased significantly from 84.62 to 95.71, representing an improvement of 11.10 points (13.11%) (p 0.001). Participants also demonstrated greater understanding of emotional regulation, positive parent-child communication, and parental role modeling. These findings indicate that the program effectively strengthened parenting literacy and has the potential to be implemented as a community-based family education initiative.